Listeria Monocytogenes as a Foodborne Pathogen: Biocontrol in Foods using Lytic Bacteriophages - Naim Deniz Ayaz; Gizem Cufaoglu (Journal of Clinical Microbiology and Biochemical Technology - Peertechz Publications, 2016)
Foods are playing a significant role in human infections because they are frequent vehicles of some human pathogens, which can spread in a short time to all the animals and are associated with cross contamination during production and processing. During stable to table, in order not to take hygienic precautions, contaminations with pathogenic microorganisms such as Listeria spp. may be occurred and consumption of such food and food products can cause foodborne illnesses. L. monoctogenes is a zoonotic foodborne bacteria that leads to a variety of serious infections in humans such as encephalitis, meningitis, abortion and septicemia, and those suffering with listeriosis occurs in approximately 30% mortality. Epidemiologic studies have revealed that a significant proportion of cases of listeriosis caused by contaminated foods. The pathogen is widely distributed in the environment and well adapted to very different environmental conditions like tolerating wide temperature (0-45°C) and pH ranges (pH 4.3-9.6) make it difficult to control food-borne infections. Although there are 13 known serotypes of L. monocytogenes, according to epidemiological studies, approximately 95% of the isolates from the food and 98% of the clinical isolates that isolated from cases of listeriosis in humans belong to 1/2a, 1/2b, 1/2c and 4b serotypes. Bacteriophages can be applied to living tissues without causing any harm due to their highly selective toxicity. This is the most important advantage when they compared with antibiotics and antiseptics. Rapidly growing bacterial resistance to antibiotics and need for development of alternative methods, increasing interest in using bacteriophages in treatment or as biocontrol agents in foods nowadays. In addition to the systems like HACCP and GMP for food safety from farm to table, the use of specifi c virulent bacteriophages for L. monocytogenes in order to reduce the bacterial load in foods of animal origin emerges as another method. It is reported that the usage of specific virulent  acteriophages to L. monocytogenes as a biocontrol and decontamination agent of L. monocytogenes in foods, don't cause any side effects in humans.